Recent advances in Co-catalyzed C–C and C–N bond formation via ADC and ATH reactions. (30th July 2021) - Zhang, Meng-Juan; Ge, Xiao-Lan; Young, David J.; Li, Hong-Xi
Abstract: Scarce precious metals commonly adopted for crucial technologies such as catalysis can potentially be replaced with inexpensive, earth-abundant metals. Cobalt is gaining attention in this respect because of its distinctive redox chemistry that is suited to catalyzing the formation of C–C and C–N bonds. Two recently developed examples are cobalt-catalyzed acceptorless dehydrogenative coupling (ADC) and auto-transfer-hydrogenative (ATH) reactions for the reliable and mild construction of these bonds. Advances in both classes of reaction are herein reviewed (2013-present). Graphical abstract: Image 1